Iterative lagged asymmetric responses in strategic management and long-range planning. (November 2019) - Simandan, Dragos
Actors in competitive environments are bound to decide and act under conditions of uncertainty because they rarely have accurate foreknowledge of how their opponents will respond and when they will respond. Just as a competitor makes a move to improve their standing on a given variable relative to a target competitor, she should expect the latter to counteract with an iterative lagged asymmetric response, that is, with a sequence of countermoves ( iteration ) that is very different in kind from its trigger ( asymmetry ) and that will be launched at some unknown point in the future ( time lag ). The paper explicates the broad relevance of the newly proposed concept of "iterative lagged asymmetric responses" to the social study of temporality and to fields as diverse as intelligence and counterintelligence studies, strategic management, futures studies, military theory, and long-range planning. By bringing out in the foreground and substantiating the observation that competitive environments place a strategic premium on surprise, the concept of iterative lagged asymmetric responses makes a contribution to the never-ending and many-pronged debate about the extent to which the future can be predicted.